Pengaruh Efikasi Diri dan Lingkungan Belajar Terhadap Hasil Belajar Siswa SMK Negeri 44 Jakarta dengan Motivasi Belajar Sebagai Variabel Mediasi - Muhamad Fathir Harsya Ruyani; Dewi Nurmalasari; Achmad Fauzi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the influence of self-efficacy and learning environment on learning outcomes, with learning motivation as a mediating variable, among students of SMK Negeri 44 Jakarta. Employing a quantitative approach with a survey method, the research involved a population of 175 students, all of whom were included as the sample through a total sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The analytical procedures encompassed measurement model analysis, structural model analysis, and hypothesis testing for both direct and indirect effects.The findings reveal a positive and significant direct effect of self-efficacy on learning outcomes, indicating that students with higher confidence in their abilities tend to achieve better academic performance. Similarly, the learning environment was found to have a positive and significant direct effect on learning outcomes, suggesting that supportive academic surroundings contribute meaningfully to student achievement. However, the study found no significant direct effect of learning motivation on learning outcomes, nor any significant mediating role of learning motivation in the relationships between self-efficacy and learning outcomes or between learning environment and learning outcomes. These results imply that while self-efficacy and a conducive learning environment are key determinants of academic success, the role of learning motivation as an intervening variable may not be as substantial in this context. The absence of mediation suggests that motivation alone may not bridge the gap between personal and environmental factors and actual academic performance. This study contributes to educational research by providing empirical evidence on the complex interplay between psychological, environmental, and motivational factors influencing student achievement, highlighting the need for educators to strengthen both self-belief and learning conditions to optimize outcomes.